Optimization of Bankruptcy Assets in the Form of Non-Fungible Token (NFT) by the Curator Based on Indonesian Bankruptcy Law - Hariyanto (International Journal of Science and Society, 2023)
This research is a normative juridical study of non-fungible token (NFT) regarding the position of NFT in relation to positive law in Indonesia, legal certainty for bankrupt assets in the form of NFT and the efforts that can be made by curators in order to optimize bankruptcy assets in the form of NFT. The results of this study indicate that NFT has met the classification of immovable and indivisible movable objects. The provisions of Article 21, Article 98 and 101 Paragraph (1) of the Bankruptcy Law have provided legal certainty to curators and bankrupt creditors that NFT is a bankrupt asset that must be optimized by the curator to pay off the debts of debtors. There are 3 main obstacles by the curator in optimizing bankrupt assets in the form of NFT, in the process of registering NFT as bankrupt assets, the process of determining the best time to sell NFT and the method of selling NFT based on the Bankruptcy Law. Against these obstacles, the Bankruptcy Law and positive law have provided efforts that can be taken by curators in the context of optimizing bankrupt assets.